Between protectionism, poverty orientation, and market efficiency: reform of the EU sugar market organization - Michael Brüntrup (Deutsches Institut für Entwicklungspolitik (DIE), 2005)
The reform of the European sugar market organization (SMO), which has until now been excepted from the general restructuring of the EU Common Agricultural Policy, must be seen as an important building block in the project of liberalizing the international agricultural markets. The reform will have substantial impacts on developing countries. However, it is not as radical as it is often made out to be: Its principle aim is to cut subsidized exports by lowering administrative prices. Some other important elements of the existing market regime will continue in place, including production quotas and heavily restricted market access. Without tariff protection, no more than a small proportion of the EU's sugar production would be likely to survive for long, and most of the EU's demand for sugar would be covered by a number of larger, competitive developing countries. For this reason alone, pressure to reform the EU sugar sector is likely to continue over the long term. Alternative reform proposals that would have left prices at their present, high levels and used quotas to manage production and imports must for this reason be viewed with a critical eye. While these proposals hold promise of short-term gains for certain developing countries, they would at the same time set major incentives for these countries to develop inefficient production structures that would not prove economically sustainable in the long run. The consequence would be later crises entailing high economic and social costs. Under the current form not all developing countries will turn out to be winners. The decline in prices it entails will substantially curtail the exports and export chances of some developing countries that presently enjoy preferential access to the EU market. These include some especially poor countries that have virtually no other production compensation for these losers of the reform – for one thing to cushion negative impacts, but for another to avoid the impression that agricultural liberalization is a factor that contributes to exacerbating poverty. The EU should mobilize the funds needed to compensate these countries.
Keywords: 330